CARDIOVASCULAR OUTCOMES OF INITIAL BETA-BLOCKER + CALCIUM CHANNEL BLOCKER THERAPY VS OTHER DUAL THERAPIES IN CHINESE PATIENTS WITH NEWLY DIAGNOSED HYPERTENSION: A REAL-WORLD STUDY. (June 2022) - Guo, Qinghui; Lin, Junxiong; Peng, Feng; Chai, Dajun; Lin, Jinxiu
Abstract : Objective: This study aimed to compare cardiovascular (CV) outcomes associated with initial beta-blocker (BB) + calcium channel blocker (CCB) dual therapy and other initial dual therapies in Chinese patients with newly diagnosed hypertension. Design and method: In this retrospective study, all patients in a regional electronic database with newly diagnosed hypertension from January 01, 2012 to December 31, 2016 who received initial dual therapy recommended by the 2018 Chinese Guidelines for Prevention and Treatment of Hypertension were included. The recommended dual therapies included BB+CCB (B+C), ARB/ACEI+C (A+C), A+Diuretic (A+D) and C+D. 1:2 PSM was used to balance baseline characteristics between patients receiving B+C and patients receiving other initial dual therapies (Others). Primary outcome was major adverse cardiovascular events (MACE) consisting of non-fatal stroke, non-fatal myocardial infarction (MI), non-fatal chronic heart failure (CHF) and all-cause death during a median follow-up of 2.02 years (IQR: 1.07–3.36 years). Cox proportional hazard models were used to compare these CV outcomes in the 2 matched cohorts. Results: After the PSM, 6, 227 patients in the B+C group and 12, 454 patients in the Others group were included. The B+C group and the Others group had comparable age (59.5 ± 12.7 years vs. 59.8 ± 12.3 years) and diastolic blood pressure (91.2 ± 6.7 mmHg vs. 91.2 ± 6.9 mmHg), although their heart rate (88.0 ± 6.8 vs. 88.4 ± 7.1) and systolic blood pressure (156.2 ± 7.0 mmHg vs. 155.9 ± 7.1 mmHg) still had differences. Compared to the Others group, the B+C group had significantly lower risks of MACE (HR 0.85; 95%CI 0.78–0.92; P < 0.001), non-fatal stroke (HR 0.89; 95% CI 0.81–0.98; P = 0.018) and non-fatal CHF (HR 0.74; 95% CI 0.63–0.86; P < 0.0001) (Figure 1). Differences in risks of non-fatal MI and all-cause death in the 2 groups were statistically insignificant. Additionally, A+D (HR 1.71; 95% CI 1.52–1.92) and C+D (HR 1.77; 95% CI 1.45–2.15) were associated with significantly higher risk of MACE than B+C, and the difference between A+C (HR 1.04; 95% CI 0.96–1.14) and B+C was small. Conclusions: BB+CCB initial dual therapy was associated with lower risks of MACE, stroke and CHF than other recommended initial dual therapies in Chinese patients with newly diagnosed hypertension.